GERAKAN MEMBUMIKAN TAFSIR AL-QUR’AN DI INDONESIA: STUDI M. QURAISH SHIHAB ATAS TAFSIR AL-MISBAH - Alwi HS, Muhammad; Arsyad, Muhammad; Akmal, Muhammad (At-Tibyan: Jurnal Ilmu Alqur`an dan Tafsir, 2020)
This article discusses the phenomenon of grounding the interpretation of the Qur'an in Indonesia by focusing on M. Quraish Shihab as a modern-contemporary interpreter who successfully interprets the Qur'an in written and oral form. The important location of M. Quraish Shihab in grounding the interpretation of the Qur'an lies in his efforts to interpret the Qur'an with language that is easy to understand but has high quality content. This makes M. Quraish Shihab always an important reference in the interpretation of the Qur'an in Indonesia, both among Al-Qur'an scholars and ordinary people. Tafsir Al-Misbah is evidence of success in grounding the interpretation of the Qur'an in Indonesia, both in the form of commentaries and studies. Kitab Tafsir Al-Misbah is the work of Phenomenal M. Quraish Shihab in simplifying the language of its interpretation, having previously been considered to be rambling on Kitab Tafsir Al-Qur'an 'Al-Karim. Meanwhile, the "Kajian Tafsir Al-Misbah" was born as an effort to maintain the understanding of the Qur'an by experts, so that the public gets enlightened understanding of the Qur'an by people who are truly in their capacity as interpreters of the Qur'an.